We can solve this simultaneous equation using the substitution method as follows:
1. Rearrange one of the equations to make one of the variables the subject, for example:
2x + 2y = 14
2y = -2x + 14
y = -x + 7
2. Substitute this expression for y into the other equation, and solve for x, for example:
5x - 2y = 14
5x - 2(-x + 7) = 14
5x + 2x - 14 = 14
7x = 28
x = 4
3. Substitute this value of x back into one of the original equations and solve for y, for example:
2x + 2y = 14
2(4) + 2y = 14
8 + 2y = 14
2y = 6
y = 3
So the solution to the simultaneous equation is x=4 and y=3.
solve the simultaneous equation: 5x - 2y=14 and 2x +2y=14. using substitution method
1 answer